Decreased Serum Thrombospondin-1 Levels in Pancreatic Cancer Patients Up to 24 Months Prior to Clinical Diagnosis: Association with Diabetes Mellitus - Jenkinson, Claire; Elliott, Victoria L.; Evans, Anthony; Oldfield, Lucy; Jenkins, Rosalind E.; O'Brien, Darragh P.; Apostolidou, Sophia; Gentry-Maharaj, Aleksandra; Fourkala, Evangelia-O; Jacobs, Ian J.; Menon, Usha; Cox, Trevor; et al. (Clinical cancer research, 2016)
Purpose: Identification of serum biomarkers enabling earlier diagnosis of pancreatic ductal adenocarcinoma (PDAC) could improve outcome. Serum protein profiles in patients with preclinical disease and at diagnosis were investigated. Experimental Design: Serum from cases up to 4 years prior to PDAC diagnosis and controls (UKCTOCS, n = 174) were studied, alongside samples from patients diagnosed with PDAC, chronic pancreatitis, benign biliary disease, type 2 diabetes mellitus, and healthy subjects (n = 298). Isobaric tags for relative and absolute quantification (iTRAQ) enabled comparisons of pooled serum from a test set (n = 150). Validation was undertaken using multiple reaction monitoring (MRM) and/or Western blotting in all 472 human samples and samples from a KPC mouse model. Results: iTRAQ identified thrombospondin-1 (TSP-1) as reduced preclinically and in diagnosed samples. MRM confirmed significant reduction in levels of TSP-1 up to 24 months prior to diagnosis. A combination of TSP-1 and CA19-9 gave an AUC of 0.86, significantly outperforming both markers alone (0.69 and 0.77, respectively; P < 0.01). TSP-1 was also decreased in PDAC patients compared with healthy controls (P < 0.05) and patients with benign biliary obstruction (P < 0.01). Low levels of TSP-1 correlated with poorer survival, preclinically (P < 0.05) and at clinical diagnosis (P < 0.02). In PDAC patients, reduced TSP-1 levels were more frequently observed in those with confirmed diabetes mellitus (P < 0.01). Significantly lower levels were also observed in PDAC patients with diabetes compared with individuals with type 2 diabetes mellitus (P = 0.01). Conclusions: Circulating TSP-1 levels decrease up to 24 months prior to diagnosis of PDAC and significantly enhance the diagnostic performance of CA19-9. The influence of diabetes mellitus on biomarker behavior should be considered in future studies. Clin Cancer Res; 22(7); 1734–43. ©2015 AACR.